Hubungan Tidur Larut Malam Terhadap Timbulnya Akne Vulgaris Pada Mahasantri Putra Pesantren International K.H Mas Mansur Ums 2015 - Primadani, Apri Anggi; , dr. Flora Ramona S.P, M.Kes.,Sp.KK; , dr. Ratih Pramuningtyas, Sp.KK (2015)
Background: Acne vulgaris is a skin disease that occurs in sebaceous follicles. The prevalence of acne in adolescence is quite high, ranging between 47-90%. Some risk factors that play an important role in the occurrence of acne in teenagers is food , cosmetics , and an increase of androgens. Sleep too late at night is expected to lead to increased the activity of androgens. Androgen hormones play an important role in the regulation of sebum production mechanism. Excessive sebum production will cause acne. Methods: This research is observational analytic types and using cross sectional design. This research was conducted at the International Islamic School of KH Mas Mansur Surakarta in January 2015. To test the hypothesis, analysis that used is Chi-Square statistics test in SPSS version 17.0. Results: The results of a study of 70 people found the results of the 35 people who sleep late 28 people (40%) suffered from acne vulgaris and 7 (10%) do not suffer from acne vulgaris. Of the 35 people who do not sleep late at night showed 10 (14.3%) suffered from acne and 25 persons (35.7%) do not suffer from acne. Conclusion: There is a correlation between sleep late night and incidence of acne vulgaris in male student of K.H Mas Mansur islamic school UMS.